Assessing the accuracy of patient report of the 5As (ask, assess, advise, assist, and arrange) for smoking cessation counseling - Susan A. Flocke; Elizabeth Antognoli (Family Medicine and Community Health, 2017)
Objective: The 5As framework (ask, advise, assess, assist, arrange) is a recommended strategy for smoking cessation counseling in primary care. This study compares patient report with direct observation to assess the degree of recall bias for each of the 5As. Methods: Primary care visits by 107 adult smokers and 16 physicians were audio-recorded. Within 48 hours after the visit, patients completed a survey assessing whether or not smoking was discussed and items specific to each of the 5As. The audio recordings were evaluated to assess the presence of each A. The sensitivity, specificity, positive predictive value, and negative predictive value of patient report versus direct observation were computed. Results: The frequency of the 5As based on evaluation of the audio recording ranged from 13% (arrange) to 98% (ask). The sensitivity and specificity of patient report were 92% and not applicable for ask, 90% and 50% for assess, 94% and 33% for advise, 90% and 50% for assist, and 85% and 67% for arrange follow-up. Positive predictive values ranged from 28% to 98%; negative predictive values ranged from 0% to 97%. Conclusion: Compared with the gold standard of direct observation, patient report of each of the 5As is reasonably sensitive but not specific. Patients overreport the occurrence of each of the 5As.